The Potential Impact of COVID‐19 on Student Learning and How Schools Can Respond. Issue 3 (23rd July 2020) - Wyse, Adam E.; Stickney, Eric M.; Butz, David; Beckler, Amanda; Close, Catherine N.
Abstract: There is no denying the impact that the coronravirus disease (COVID‐19) outbreak has had on many aspects of our lives. This article looks at the potential impact of COVID‐19 on student learning as schools abruptly morphed into virtual learning environments using data from several instructional, practice, and assessment solutions offered by Renaissance. First, three hypothetical learning scenarios are considered using normative data from Star assessments to explore the potential impact on reading and math test performace. Next, data on Focus Skills are used to highlight which grades may have missed the most foundational math and reading content if instruction was stopped or reduced. Last, data from two of Renaissance's practice tools are used to evaluate whether students were practicing key skills following school closures. The article concludes that academic decline will likely occur but may be tempered by the increased use of practice tools; effects may look different for math and reading; and may impact grades and schools differently. As such, schools may need to leverage decision‐making frameworks, such as the Multi‐tiered Systems of Support/Response‐to‐Intervention (MTSS/RTI) framework, more than ever to identify needs and target instruction where it matters most when school begins in fall 2020.